Kebijakan Pengelolaan Sampah Pada TPST3R-GMJB (Tempat Pengelolaan Sampah Terpadu Reduce-Reuse-Recyle Gerakan Muara Jawa Bersih) di Kecamatan Muara Jawa Kabupaten Kutai Kartanegara - Kresna, Adi; Kusuma, Aji Ratna; Paselle, Enos (Universitas 17 Agustus 1945 Samarinda, 2024)
This research aims to determine waste management at TPST3R-GMJB in Muara Jawa District, Kutai Kartanegara Regency and factors that inhibit waste management at TPST3R-GMJB in Muara Jawa District, Kutai Kartanegara Regency. This research is a study that produces descriptive data in the form of written words of people and behaviors observed systematically and accurately, directed at the background and the individual holistically (intact) without making comparisons with other variables. Based on the analysis of the results of Waste Management research at TPST3R-GMJB in Muara Jawa District, Kutai Kartanegara Regency, it can be concluded that waste collection activities carried out by TPST3R-GMJB in Muara Java District have not been optimal, waste transportation activities at TPST3R-GMJB in Muara Java District have not run well. The main cause is the supporting factors of transportation activities, namely garbage transport vehicles in poor condition (often damaged), Waste processing activities at TPST3R-GMJB in Muara Jawa District have not been maximized, because most machines / equipment in processing waste have not been supported by better equipment (modern) and the volume produced is also not optimal, the final waste disposal activities carried out by TPST3R-GMJB in Muara Jawa District have not been said to be good, and inhibiting factors for waste management at TPST3R-GMJB in Muara Jawa District, among others, namely waste collection, waste transportation. TPST3R-GMJB garbage transport fleet in the form of dump trucks in poor condition (often damaged), waste processing. The waste processing equipment (machines) at TPST3R-GMJB are still mostly simple equipment and the support of electricity supply to operate the equipment is also not optimal, Final Disposal. Financing and technology that are less supportive in handling waste in landfills (TPA).